Isolation, identification, and potentiality of gut-derived probiotic bacteria from Heteropneustes fossilis, stinging catfish - Jilani, Abdul Kader; Haider, Md Nurul; Hasan, Abir; Mahfuz, Md Adil; Rifat, Md Nazmul Islam; Hossain, Md Mubarack; Hasan , Muhammad Mehedi (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study was conducted to isolate and identify probiotic bacteria from wild stinging catfish (Heteropneustes fossilis), a very popular high-valued aquaculture species of Bangladesh. The isolates were identified through conventional culture-based and molecular techniques. Materials and Methods: Stinging catfish harvested from natural sources of three sampling sites under two districts (Kishoreganj and Netrakona) were collected, dissected for gut content, and cultured onto Lactobacillus MRS Agar plates. Out of 60 bacterial isolates obtained, 10 were chosen for an in vitro evaluation of their probiotic potentials through pH and bile tolerance tests. The 16S rRNA gene sequences of the selected isolates were searched against the NCBI database using the Basic Local Alignment Search Tool for Nucleotides (BLASTNs). Results: The isolates were identified as Staphylococcus arlettae, Bacillus subtilis, Staphylococcus succinus, Bacillus velezensis, Kocuria subflava, Macrococcus caseolyticus, Lysinibacillus sphaericus, Glutamicibacter mysorens, Bacillus cereus, and Acinetobacter lwoffii. Among them, B. subtilis, S. succinus, B. velezensis, M. caseolyticus, G. mysorens, and B. cereus exhibited notable growth across all tested pH levels (pH 2, 3, and 4) and bile salt concentrations (0.3%, 0.5%, and 1.0%) suggesting that they have strong potential as probiotic bacteria. In addition, S. arlettae also indicated promising growth except at pH 2. L. sphaericus and K. subflava exhibited limited growth at low pH but tolerated bile salt concentrations. A. lwoffii did not show any growth at pH tests but minimal growth at the lower concentrations of bile salts. Conclusion: According to the potentiality assessments and previous literature reviews, five isolates such as B. subtilis, S. succinus, M. caseolyticus, G. mysorens, and B. cereus were identified as potential probiotic bacteria. As species-specific probiotics are considered to perform more effectively and efficiently than unknown-sourced commercial probiotics, the findings of this study will be applicable in enhancing the aquaculture production of stinging catfish. J. Adv. Vet. Anim. Res., 11(3): 560-572, September 2024 http://doi.org/10.5455/javar.2024.k806